2015
DOI: 10.1248/bpb.b15-00567
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Antiinflammatory Effect of a Novel Gel System Containing Ketoprofen Solid Nanoparticles

Abstract: We previously reported that dermal application using nanoparticles improves skin penetration. In this study, we prepared novel topical formulations containing ketoprofen (KET) solid nanoparticles (KET nano gel ointment) and investigated the antiinflammatory effect of the KET nanoparticle formulations on rheumatoid arthritis using adjuvant-induced arthritis (AA) rats. The KET nano gel ointment was prepared using a bead mill method and additives including methylcellulose and Carbopol 934; the mean particle size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…However, the plasma concentration following the administration of the TL nano -and KET nano -gel formulations was higher than that following the administration of the TL micro and KET micro -gel formulations. In addition, the plasma concentration following the administration of the TL nano -and KET nano -gel formulations was lower than that following the administration of the ointments containing the dissolved drugs commercially available ointments 11,13 . It has been reported that drug solubility can be expected to be enhanced at particle sizes less than 100 nm 28 .…”
Section: Pharmacokinetic Analysis Of Gel System Containingmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the plasma concentration following the administration of the TL nano -and KET nano -gel formulations was higher than that following the administration of the TL micro and KET micro -gel formulations. In addition, the plasma concentration following the administration of the TL nano -and KET nano -gel formulations was lower than that following the administration of the ointments containing the dissolved drugs commercially available ointments 11,13 . It has been reported that drug solubility can be expected to be enhanced at particle sizes less than 100 nm 28 .…”
Section: Pharmacokinetic Analysis Of Gel System Containingmentioning
confidence: 87%
“…These results were the same as the current results for the IBU-gel formulations. In addition, in the in vitro skin penetration experiments, the penetration rate of the IMC nano -186 nm , KET nano -83 nm gel formulations mean particle size was higher than that of an ointment containing dissolved IMC, KET commercially available IMC-gel formulations IDOMETHINE KOWA gel 1 , KET-gel formulations SECTOR gel ® 3 12,13 , Taken together, we hypothesize that drug infiltration into the skin tissue is enhanced for particles in the size range of approximately 80-200 nm in comparison with drugs in the liquid state, and this increase in drug infiltration may cause the high skin penetration and drug accumulation in the skin tissue for the nano gel formulations. In contrast to the results in skin penetration and drug accumulation in skin tissue, the plasma concentration behavior of the TL nano -, KET nano -gel formulations differed from that of the IMC nanogel formulation in in vivo percutaneous absorption experiments 11 13 .…”
Section: Pharmacokinetic Analysis Of Gel System Containingmentioning
confidence: 96%
“…A sheet of CLZ gel patches (0.3 g) and gel ointment was fixed on the shaved abdominal skin with an adhesive and immediately occluded with adhesive tape. Venous blood (100 µl) was collected from the jugular vein through the cannula between 0 and 48 h after the application of the CLZ gel patches and gel ointment (18). The blood was centrifuged at 15,000 rpm for 20 min at 4˚C to obtain, plasma, which was stored at -80˚C until analysis.…”
Section: Analysis Of Pharmacokinetics Of Clz In Ratsmentioning
confidence: 99%
“…Lecithin is disorganize the structure of the skin, transiently it opens the pores of the skin and increase the penetration of drugs Fig. 1 10 . But the exact mechanism how lecithin alters the skin is not yet understood clearly.…”
Section: Mechanism Of Action Of Plos Through Skinmentioning
confidence: 99%